Mitigating climate change through the income tax legislation : a brief analysis of section 12K of the Income Tax Act no. 58 of 1962 and its implications for South African CDM projects - Garrod, Yashaswini (Department of Commercial Law, 2014)
[This] dissertation is dedicated to this attempt of making South Africa a more environmentally sustainable economy through the development of new CDM projects. This dissertation examines the introduction of section 12K in the Income Tax Act 58 of 1962 and how this novel incentive interacts with our current income tax legislation. This dissertation highlights some issues surrounding the section 12K exemption which may detract from its true potential and proposes ways to resolve these issues in order to make this incentive more attractive to the CDM project developers.